Acurácia da tomografia computadorizada de feixe cônico e a influência do tamanho do voxel na identificação de lesão de furca em molares superiores - Oliveira, Paula Renata Damaceno (2018)
Furcation lesion, bone loss in the region of the multiradicular teeth, is a big challenge in the treatment of patients with periodontitis. The aim of this study was to compare the accuracy of CBCT and the influence of voxel size on the identification of furca lesion in upper molars. This was a cross-sectional observational study, which the sample consisted of 120 sites with chronic periodontitis from 12 patients with periodontits, in whom scrapie access surgery and CBCT were indicated for the treatment of periodontal disease. The same periodontist made the clinic diagnostic of presence and absence of furcation lesion, horizontal bone loss and vertical bone loss. The CBCT images were obteined with I-CAT Cone Beam 3D Imaging System - Next Generation (Imaging Sciences International, Hatfiels, PA, USA), with isometric voxel of 0.125 mm 3; FOV of 8 x 8 cm, 120 kV and 5 mA current, and acquisition time of 26.9 s. Subsequently, the images were reformatted in other sizes of voxel (0.200 mm 3 and 0.250 mm 3), and evaluated by three experienced radiologists, previously calibrated. Transurgical, clinical and radiographic measurements were performed in a similar way and at the same sites. Cohen's Kappa, Intraclass Coefficient, McNemar and Wilcoxon tests were performed.The level of significance was set at 5% (p <0.05). In the evaluation of vertical bone loss, the intra-examiner agreement (ICC between 0.805 and 0.916) and inter-examiner (ICC between 0.754 and 0.965) were excellent for vertical bone loss. Regarding the presence or absence of the defect, it was good (k: 0.615) to very good (k: 1,000) in intra-examiner agreement, and was good (kappa between 0.619 and 0.773) for inter-examiner agreement. For horizontal bone loss, it was moderate (k: 0.424) to very good (k: 1,000) in intra-examiner agreement, and moderate (kappa between 0.463 and 0.590) for inter-examiner agreement. The 0.125 mm³ voxel presented the best agreement for all evaluations. Compared with the different sizes of voxel with the gold standard, statistically significant difference (p <0.05) was observed at the distal site, and it was easier for the examiners to diagnose furcation lesions at this site. The CBCT for the diagnosis of incipient furcation defects, showed an accuracy of 75%, demonstrating a greater specificity of the imaging tests in detriment of sensitivity. The clinical evaluation showed a greater sensitivity, 80%, in the detection of furcation defects, showing the importance of a good evaluation for the diagnosis and treatment of patients in this condition. The tomographic measurement at the distal site showed greater proximity with surgical measurement. When tomographic image is required for furcation evaluation, the smaller voxel should be preferred because it presents better results.